1994
DOI: 10.4098/at.arch.94-51
|View full text |Cite
|
Sign up to set email alerts
|

Cervus canadensis and C. elaphus : North American subspecies and evaluation of clinal extremes

Abstract: The distinctiveness of each extant North American subspecies of C. elaphus (Linnaeus, 1758) was tested using craniometric data. To provide a context for interpretation of these data, the distinctiveness of North American C. elaphus from Eurasian C. elaphus was reassessed from existing data and conclusions tested. Morphometric variations in size, shape, and sexual dimorphism of adult crania were analyzed using combined male-female and independent male and female principal component analyses. North American subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Lumping the Eastern (C. e. canadensis), Merrium (C. e. merriami), Rocky Mountain (C. e. nelsoni), and Manitoban (C. e. manitobensis) populations found in North America under canadensis (Groves and Grubb, 1987) is supported by this work as well as recent by studies by Schonewald (1994), Polziehn et al (2000). MtDNA sequence differences were unable to differentiate wapiti sampled from the historic range of the Eastern wapiti in Ontario from Rocky Mountain or Manitoban wapiti, whereas Roosevelt wapiti (C. e. roosevelti) from Vancouver Island and Tule wapiti (C. e. nannodes) from California appear to be distinct subspecies (Denome, 1998;.…”
Section: Intraspecific Diversity Of Wapitisupporting
confidence: 67%
“…Lumping the Eastern (C. e. canadensis), Merrium (C. e. merriami), Rocky Mountain (C. e. nelsoni), and Manitoban (C. e. manitobensis) populations found in North America under canadensis (Groves and Grubb, 1987) is supported by this work as well as recent by studies by Schonewald (1994), Polziehn et al (2000). MtDNA sequence differences were unable to differentiate wapiti sampled from the historic range of the Eastern wapiti in Ontario from Rocky Mountain or Manitoban wapiti, whereas Roosevelt wapiti (C. e. roosevelti) from Vancouver Island and Tule wapiti (C. e. nannodes) from California appear to be distinct subspecies (Denome, 1998;.…”
Section: Intraspecific Diversity Of Wapitisupporting
confidence: 67%
“…However, the white-lipped deer (Przewalskium albirostris), which is accepted as being quite different from deer of the genus Cervus, shares remarkable similarity in the external appearance and antler mass with wapiti (Geist, 1987). While cervids may appear phenotypically similar, Lowe and Gardiner (1989) and Schonewald (1994) found that skeletal measurements placed red deer and wapiti into separate clades. UPGMA analysis of protein data from 28 loci also separated red deer from wapiti (Dratch and Gyllensten, 1985) and the RFLP analysis of complete mtDNA separated a Mongolian wapiti from the North American wapiti (Cronin, 1992).…”
Section: Resultsmentioning
confidence: 98%
“…A panmictic or clinal distribution was suggested for eastern, Manitoban, and Rocky Mountain wapiti (Bryant and Maser 1982;Schonewald 1994). With a few exceptions, Schonewald (1994) found a decrease in cranial size from north to south and from western Europe to North America.…”
Section: Discussionmentioning
confidence: 99%